What Do We Want Students to Know from Being Taught a Poem?. Issue 1 (2nd January 2021) - Sawyer, Wayne; McLean Davies, Larissa
ABSTRACT: This paper uses a Gwen Harwood poem to open up questions of "knowing" around the teaching of Literature. Following our own brief reading of the poem, we particularly discuss ways in which questions of knowing/knowledge have been considered in Literature teaching historically, such as: - the binary of "knowledge" and "experience" - the role of the cognitive in teaching/studying Literature - forms of knowing that include the aesthetic and affect - how knowledge might be "made" in the Literature classroom: the role of pedagogy and the question of "producing culture" The article concludes with a discussion of how such issues have arisen in a set of interviews with a small number of teachers in Australia and England. Their views on the teaching of Literature help us reflect on the knowledge issues opened up earlier in the article.